MENINGKATKAN KETERAMPILAN MERIAS WAJAH PANGGUNG MELALUI TEHNIK MODELLING BAGI ANAK TUNARUNGU KELAS XI DI SLB NEGERI TANJUNGPINANG - Santy - Kurniawaty (Jurnal Penelitian Pendidikan Khusus, 2013)
The study was caused by the students difficulties in stage make up ability, that‘s why the direct modeling. The aims of this research is to increase the students competency in stage make up by the direct modeling techniques. Modeling techniques is a teaching method by doing some demonstrated scenario by the students in front of the class, profesionalism skill and competency were expected. Modeling tehniques was used to make the observation, collecting data treatment and analize earned clearly by the students. The research useh classroom action research approach with collaborated with the other teachers. There are four research subject. They are the teaching ( as the researcher ) and the students of SMALB at SLB Negeri Tanjungpinang grade XI . According to the research result, Teaching metode by using modelling teaching ue able to increase the students competency in stage make up. It was showed from each subject test result protost result stated that the stage make up competency were: AG (35%), DL ( 35%) and FKD (34%). By going the modelling technig ue approach, the students competency were raised (AD 93%), DL (91%) and FKD (88%). This result showed each subject has a good competency in stage make up reach the very high scored level. it was conclude that the research subjects (AG, DL and FKD) mastering the stage make up competency. Subject research need to improve the ability by continuous exercise frequency by using make up equipment property.